Sodium-reduced lean sausages with fish oil optimized by a mixture design approach - Marchetti, Lucas (2015)
A partial NaCl replacement by KCl and sodium tripolyphosphate on low-fat meat sausages formulated with fish oil was studied using a mixture design. Thermal behavior by modulated differential scanning calorimetry, physicochemical, and textural propertieswere determined; afterwards they were mathematically modeled as a function of salts content. The thermo-rheological behavior of the different formulationswas also studied in a controlstress rheometer. The optimal sodium reduction was found employing a desirability function approach. This formulation was experimentally validated and employed for microstructure analysis by environmental scanning microscopy. The results obtained in this work revealed that partial sodium replacement affected the matrix microstructure, but this change had no impact on sensory acceptability. In comparison with US and Argentinean commercial sausages, our product has 58% and 70% less Na+ respectively.